A Study Of Optimization For Surface Finish On Drilling Process Of AISI D2 Tool Steel - Osman, Mohd Hairizal; Ab Rahman, Mohd Hidayat; Ahmad, Mohd Nazri; Wahid, Mohammad Khalid; Maidin, Nurul Ain (Research India Publications, 2017)
This research was carried out to determine the optimization parameter for holes diameter accuracy in dry drilling process of AISI D2 Tool Steel using Taguchi method.The objective of this project is to find the optimum condition in producing high accuracy of holes diameter.The selected spindle speeds for drilling process are 482 RPM,550 RPM and 627 RPM.The feed rate parameters are 68 mm/min,103 mm/min and 146 mm/min.Next parameter is the types of drill bit which consist of High Speed Steel (HSS) coated with Titanium Nitride (TiN),High Speed Steel (HSS) coated with Titanium Carbon Nitride (TiCN) and High Speed Steel (HSS) coated with Titanium Aluminium Nitride (TiAlN).The machining process will be performed on the CNC milling machine.The diameter accuracy of holes will be tested by using Coordinate Measuring Machine (CMM).